Island biogeography: colonization, evolution, and excitation; analogy and potential implication to oncology - Ofer N. Gofrit (Frontiers in Ecology and Evolution)
Life on islands and cancer evolves under unique environmental pressures and acquire distinctive features. This manuscript is an attempt to find analogies between carcinogenesis and island biota colonization, evolution, and extinction. Hopefully this analogy will provide hints how extinct cancer. Both island biota and malignancy are initially scarce in number and genetic variation, and both experience rapid increase in genetic variability without mandatory environmental pressures. Island evolution follows two main pathways: anagenesis-linear speciation that fits the course of benign tumors, and cladogenesis-branching speciation that match malignant progression. Both island biota and most cancer types develop giantism compared to their mainland equivalents and normal cells of origin. Island biota is prone to extinction, but not all species are equally sensitive. Susceptible species exhibit low genetic diversity and long breeding cycles. Cancer cells habitually exhibit opposite features. Prolonging cancer cell cycle (by hormonal, pharmacological, or genetic manipulations) can potentially make cancer cells more prone to extinction by other interventions. Further studies of the similarities between island evolution and carcinogenesis may reveal additional intervention points.